The Role of Muslim Women in Fighting Corruption - Raden Nurhayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the role of women in combating corruption. Efforts that must be made by women to play a maximum role in combating corrupt behavior must be planned and systemic efforts, namely: First, it is necessary to build a shared awareness within the Muslim community, that women are complete human beings who are assets and have the potential to build the community. Women were also created to be Khalifah Fil-Ardh, namely as managers on earth together with men, who must be responsible for themselves, to other humans and most importantly to Allah SWT. Second, improve the quality of education both formal and non-formal, and be involved in the interests of all aspects of life. Third, it is necessary to emphasize a shared commitment to all elements of society, both men, women, rich and poor, officials and ordinary people that corruption is a crime against humanity and is a major sin, every element of society must have a part and take a clear role in efforts to eliminate corrupt behavior in their respective scopes.